Kajian Pencahayaan pada Interior Sociolla Paskal23, Bandung - Kristina Kristina; Tessa Eka Darmayanti; Stella Sondang (IMAGIONARY, 2022)
Space is the main element in the interior and lighting is one of the important factors in space design. Lighting is also a role of lighting is no longer just to provide lighting but also to highlight the aesthetics and atmosphere of the room, it can even affect the image of the interior and the experience of the individual who is in it. Many types of lighting can be applied to an interior room and it depends on what kind of atmosphere you want to display. This study aims to determine the comfort of visitors based on their experience in retail interiors at Sociolla Paskal 23 Bandung. This qualitative and quantitative research was carried out by conducting surveys, interviews, and distributing questionnaires, and using a spatial experience theory approach. The contribution of this research is to provide knowledge about the importance of lighting as a form of space and about retail interior artificial lighting that can affect one's experience.